Epistaxis first-aid management: a needs assessment among healthcare providers - Leigh Sowerby; Chandheeb Rajakumar; Matthew Davis; Brian Rotenberg (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Purpose To perform a needs assessment of epistaxis first-aid measures practiced by family physicians and Emergency Department (ED) staff in London, Ontario, Canada. Methods Paper-based multiple-choice questionnaires were distributed to participants. Participant recruitment was conducted in two parts: 1) 28 Emergency Medicine (EM) attending physicians, 21 resident physicians training in the ED, and 26 ED nurses were surveyed while on duty in the ED; 2) 27 family physicians providing walk-in or urgent care and attending a continuing medical education (CME) event were also surveyed. Respondents were asked to identify where to apply compression to the nose and how patients should be positioned during acute epistaxis. Results Regarding where to apply compression, 19% of family physicians, 43% of EM physicians, 24% of residents, and 8% of ED nurses responded correctly. Regarding positioning, all groups responded similarly with 54–62% responding correctly. Twenty-one percent of emergency physicians, 19% of residents, 11% of family physicians, and 4% of nurses responded correctly to both questions. Conclusions Most family physicians, EM attending physicians, ED nurses, and residents could not correctly identify basic first-aid measures for acute epistaxis. This study identifies an area where knowledge is lacking and the potential for improvement in patient management and education. Grapical Abstract